Relationship Between Central Artery Stiffness, Brain Arterial Dilation, and White Matter Hyperintensities in Older Adults: The ARIC Study—Brief Report. Issue 6 (June 2021) - Caughey, Melissa C.; Qiao, Ye; Meyer, Michelle L.; Palta, Priya; Matsushita, Kunihiro; Tanaka, Hirofumi; Wasserman, Bruce A.; Heiss, Gerardo
Abstract : Objective: Nonatherosclerotic outward remodeling of the large intracranial arteries may facilitate propagation of excessive aortic pulsatile energy into the cerebral microcirculation and has been associated with adverse cognitive outcomes. We sought to determine the relationship between central artery stiffness, brain arterial diameters, and white matter hyperintensity (WMH) volume in the general population of older adults. Approach and Results: We examined data from 1275 stroke-free participants of the ARIC (Atherosclerosis Risk in Communities) study (59% female, 30% Black, mean age 77 years) who underwent carotid-femoral pulse wave velocity (cf-PWV) testing and brain magnetic resonance imaging. A cf-PWV >12 m/s was considered elevated. Relationships between WMH and arterial diameters at the M1A1 segment of the middle and anterior cerebral arteries (whichever larger) were analyzed in the absence of artery-specific plaque, adjusting for intracranial volume and potential confounders. The average cf-PWV was 11.7 m/s and WMH volume was 11.2 cm 3 . Each 0.5 mm increment in M1A1 diameter was associated with 24% greater WMH volume in participants with elevated cf-PWV (exponentiated β=1.24 [95% CI, 1.12–1.36]), compared with a 10% greater WMH volume in participants without elevated cf-PWV (exponentiated β=1.10 [95% CI, 1.01–1.19]), P value for interaction=0.04. Conclusions: In this examination of older adults from the general population, larger, plaque-free arterial diameters in the middle cerebral circulation were associated with greater WMH volume, particularly among participants with elevated central artery stiffness. Strategies to reduce central artery stiffness may mitigate the association between cerebrovascular outward remodeling and microvascular damage.